Ethical Climate and Citizen Satisfaction in Informal Service Delivery in Nigeria - Shittu, Kamar Ismail; Fidelis, Freda Ijanada (Departemen Ilmu Administrasi FISIP UNHAS, 2026)
Dynamism is a critical nature of business environment that is deeply enrooted in shifts in paradigms, and this shift has in recent times emphasized on the need to place great priority on the satisfaction of customers for business success. In this vein, businesses have clearly explored various options in achieving this objective, but less attention has been to given latent options which includes ethical climate most especially in the area of artisans. This study thus investigates effect of ethical climate and customer satisfaction among auto mechanics in Minna metropolis. The study focuses on four dimensions of ethical climate: trustworthiness, transparency, fair treatment, and professional competence. Customer satisfaction is evaluated through measures of overall satisfaction and willingness to recommend auto mechanics to other car owners. The research employs a quantitative approach, utilizing a structured questionnaire to collect data from 402 registered car owners. The collected data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the associations between ethical climate dimensions and customer satisfaction. The results reveal captivating insights into the dynamics at play. Transparency, fair treatment, and professional competence demonstrate statistically significant positive relationships with customer satisfaction. However, the dimension of trustworthiness displays a positive relationship with customer satisfaction that lacks statistical significance. The findings underscore the importance of nurturing a robust ethical climate within the auto mechanic industry to enhance customer satisfaction. It is recommended that auto mechanics, through their associations, prioritise initiatives aimed at strengthening ethical dimensions. Such initiatives can include continuous improvement programmes and ethical awareness campaigns. By emphasizing these aspects, auto mechanics can create an environment that not only ensures their own professional growth but also enriches their interactions with customers, fostering trust and loyalty.